The Sustainable Future: Solid Waste Management and Sustainable Development in the Peruvian Amazon - Renan, Saavedra-Sandoval; Mabel, Contreras-Julián Rosa; Eunice, Maldonado-Lozano Amelia; Karl, Whittembury-García (Journal of Ecohumanism, 2024)
The research is important because it allows us to reflect and seek successful management of solid waste to achieve sustainable development in the Amazon region of Peru, as a constant form of protection of health and life; at the same time, becoming an incentive for family economies. The study sought to establish a relationship between solid waste management and sustainable development in the Peruvian Amazon. The type of basic research, with a non-experimental design, correlational scope and cross-sectional, whose population was 8,000 thousand users and the sample was 1,000 thousand. The data collection technique was the survey and the questionnaire was used as an instrument. The results found: The level of solid waste management is low at 60.1%. The level of sustainable development is low with 52.5%. There is a low and significant positive correlation between the dimensions permanent external conditions, institutional condition, waste treatment, collection - transportation and final disposal of the variable solid waste management and the variable sustainable development with a Spearman’s Rho coefficient of 0.342; 0.325; 0.063; 0226; 0.239 and a p-value of 0.000, significance level of 0.001. It was concluded that, There is a low and significant positive correlation between the solid waste management variable and sustainable development in the Peruvian Amazon, with a Spearman’s Rho of 0.309 and a p-value of 0.000, which is < 0.01; Others, it only has a variability of 30% between variables.